The Influence of Organizational Culture, Information Technology, Work Environment and Compensation on Employee Performance Which is Moderate by Work Motivation at PT XYZ - zuleha, arisnani; Sawitri, Ni Nyoman; Hendayana, Yayan (Dinasti Publisher, 2024)
In the national medium-term development plan (RPJM) for 2020 to 2024, the achievement of the vision for 2045 is through economic transformation supported by industrial downstreaming by utilizing human resource development. Currently, human resources are recognized as resources that create valuable competitive advantages for organizations, because employees provide human experience and human capital as well as human intellectuals for achieving organizational goals which will contribute value to the long-term sustainability of the company's business, both for the interests of shareholders and stakeholders. In this research, we analyze the influence of organizational culture, information technology, work environment and compensation on employee performance which is moderated by work motivation. This research is a quantitative research method where the objects used are permanent employees who work at PT XYZ. The number of samples used was 170 respondents. Data collection through questionnaires and data analysis techniques used in hypothesis testing using Sem Smart PLS Version 4.0.9. The results of this research indicate that (1) Organizational culture has a significant influence on employee performance (2) Information technology has no influence on employee performance (3) The work environment has no influence on employee performance (4) Compensation has no influence on employee performance ( 5) Work motivation moderates the influence of organizational culture on employee performance (6) Work motivation moderates the influence of information technology on employee performance (7) Work motivation moderates the influence of the work environment on employee performance (8) Work motivation moderates the influence of compensation on employee performance (9) Work motivation has a significant influence on employee performance. It is hoped that this research can provide input so that in the future, human resource development can pay more attention to factors that can improve performance so that employees can contribute optimally to the company's progress.